Novel and efficient one-pot five- and six-component reactions for the stereoselective synthesis of highly functionalized enaminones and dithiocarbamates - Bararjanian, Morteza; Balalaie, Saeed; Rominger, Frank; Movassagh, Barahman; Bijanzadeh, Hamid Reza (Molecular diversity, 2011)
Efficient methods for stereoselective synthesis of polyfunctional (E)-enaminones and (Z)-dithiocarbamates via one-pot five- and six-component sequential Ugi/Nucleophilic addition reactions are described. High yields and high bond forming efficiency, and simple operations are the advantages of this method.
Gesehen am 17.02.2022
First published: 12 November 2010